Early Voter Engagement Through Smart Voting Movement RRI Makassar - Fitriyani, Fitriyani; Wulandari, Ratna (PPSDP International Journal of Education, 2024)
General elections target novice voters as a flying vote. Novice voters are those who are eligible to participate in general elections for the first time with a minimum age of 17 years. Among them are class XII SMA/MA or new students. In the 2024 General Election, novice voters as a whole dominated the permanent voter list (DPT) with a number reaching around 56.45% of the total voters. However, the level of voter participation has decreased, due to disappointment in the results of previous elections and local elections. Various problems have resulted in a decrease in voter participation, including the tendency of pragmatic political elites who do not want to know about citizens' participation rights. In order to increase public confidence in domestic democracy, a strategy to increase political participation is needed. The development of Indonesian politics must be known to all citizens, in order to understand the correct political choices and in accordance with decisions without tendency and intimidation according to applicable rules. The research method used is descriptive qualitative method, because it explores the phenomenon in depth. The Smart Choosing Movement (GCM) is effective in increasing political awareness among first-time voters. GCM succeeded in raising awareness of the importance of elections, government functions, and rights and responsibilities as citizens. GCM is effective in increasing understanding of the electoral process, from registration to voting. The program is able to increase the motivation of novice voters to be directly involved in elections.